2018
DOI: 10.15835/nbha47111221
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Chemical and Antioxidant Properties of Fresh and Dried Rosehip (Rosa canina L.)

Abstract: This work aimed to evaluate the nutritional and functional properties of rosehip from Serbia. In respect to that, the content of twenty-three elements in the rosehip along with the soil were determined by inductively coupled plasma-optical emission spectroscopy and the bioaccumulation factor (BAF) was calculated. The total dry matter, water activity, and the contents of vitamin C, total phenolics and flavonoids were determined. The antioxidant ability of fresh and dried samples was evaluated using 1,1-diphenyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
29
3
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 20 publications
2
29
3
1
Order By: Relevance
“…The TPC recorded in this study for the pressed rosehip seeds was much higher than that of the rosehip fruits in Paunovic et al (2019). The rosehip seeds constitute a larger portion of the rosehip fruits, hence the TPC of the pressed seeds in our study is greater.…”
Section: Total Phenolic and Flavonoid Contentcontrasting
confidence: 51%
See 2 more Smart Citations
“…The TPC recorded in this study for the pressed rosehip seeds was much higher than that of the rosehip fruits in Paunovic et al (2019). The rosehip seeds constitute a larger portion of the rosehip fruits, hence the TPC of the pressed seeds in our study is greater.…”
Section: Total Phenolic and Flavonoid Contentcontrasting
confidence: 51%
“…The TFC of the ethanolic extract of the pressed rosehip seeds in this study was found to be higher than that of all the extracts from rosehips reported by [24]. Similarly, Paunovic et al (2019) also reported the TFC of the ethanolic extracts of fresh and dried rosehips [25]. The TFC of the fresh and dried fruits was found to be 38.52±0.82 and 26.47±1.03 mg QE/g DW, respectively [25].…”
Section: Total Phenolic and Flavonoid Contentsupporting
confidence: 48%
See 1 more Smart Citation
“…6,7,[14][15][16][17][18] Recently, breeding programs of different Rosa species have been focused on the quality and quantity of phytochemical compounds such as vitamin C and the phenolic composition in rosehips. [19][20][21][22] In recent years, global trends show that the use of rosehips and their products is increasing. 23 The inclusion of wild species that have valuable compounds is important and necessary in breeding programs.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown the genetic diversity of different Rosa species based on phytochemical diversity . Recently, breeding programs of different Rosa species have been focused on the quality and quantity of phytochemical compounds such as vitamin C and the phenolic composition in rosehips . In recent years, global trends show that the use of rosehips and their products is increasing .…”
Section: Introductionmentioning
confidence: 99%